Cenarizações dos processos de reintegração familiar : compondo redes de cuidado e afeto - Freitas, Vitor Benevenuto de (2017)
What happens in Family Reintegration Processes in Institutional Care Services for Children and Adolescents? How do these processes happen in the Vitória City/ ES? These were the questions that moved us and launched us into the field of intervention research. To that end, we called for intercessors and their theoretical-methodological contributions: Vinciane Despret, Bruno Latour, Maturana and Varela, Deleuze, Márcia Moraes, Virginia Kastrup (among others) and the female workers who work in the reception services, psychologists and social workers. We understand that the female workers are actors that, in their daily activities, weave networks in the practices of Social Assistance. The actors from two Houses of Care for Children and Adolescents in Protective Measure of the Municipality of Vitória were participants in the exercises of Researching WITH, which materialized in the recording of the events of the network in the collective field diary, in which numerous and distinct voices attended. The networks woven by the practices of Social Assistance fabricate worlds, updating historical practices and discourses and mobilizing affections capable of producing new ways of acting and thinking. Affects, therefore, are the motors for life's infinite possibilities of reinventing itself, which gives us an ethical-political commitment to care and acceptance of the various ways of life to express it. We understand that family reintegration begins in the first interventions with the family and that it is sustained by a sensitive look and body that allows to affect and to be affected through the meetings. Accompanying the network of care and affection networks, giving visibility to the network through cenarizationsevents, favored us to break with a logic of attention centered on the guardianship and blame of poor families, thus denaturalizing crystallized truths. The bet that moved this dissertation was experiencing new perspectives of care that emerge in the act, widening looks and sensibilities: a belief in the power of life.